2018
DOI: 10.1038/s41386-018-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

Social anhedonia in major depressive disorder: a symptom-specific neuroimaging approach

Abstract: While research concerning brain structural biomarkers of major depressive disorder (MDD) is continuously progressing, our state of knowledge regarding biomarkers of specific clinical profiles of MDD is still limited. The aim of the present study was to investigate brain structural correlates of social anhedonia as a cardinal symptom of MDD. In a cross-sectional study, we investigated n = 166 patients with MDD and n = 166 matched healthy controls (HC) using structural magnetic resonance imaging (MRI). Social an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 54 publications
5
25
0
Order By: Relevance
“…Unfortunately, we did not utilize a validated, multi-item self-report assessment of irritability to provide empirical support for a potential link between elevated habenula activity following negative feedback and higher levels of irritability Linking such brain alterations with a clinically-relevant construct, we observed that the higher an individual smoker's session-specific habenula activity was, the greater their state-level of tobacco craving was during that same scanning visit. Habenular structural and functional alterations have previously been linked with major depressive disorder [47,[74][75][76], a condition in which smokers are overrepresented [77] and in which social anhedonia has been regarded as an endophenotype [78,79]. Consistent with these prior observations, we observed that the higher an individual participant's session-specific habenula activity was, the greater their selfreported social anhedonia also was during that same scanning visit.…”
Section: Discussionsupporting
confidence: 88%
“…Unfortunately, we did not utilize a validated, multi-item self-report assessment of irritability to provide empirical support for a potential link between elevated habenula activity following negative feedback and higher levels of irritability Linking such brain alterations with a clinically-relevant construct, we observed that the higher an individual smoker's session-specific habenula activity was, the greater their state-level of tobacco craving was during that same scanning visit. Habenular structural and functional alterations have previously been linked with major depressive disorder [47,[74][75][76], a condition in which smokers are overrepresented [77] and in which social anhedonia has been regarded as an endophenotype [78,79]. Consistent with these prior observations, we observed that the higher an individual participant's session-specific habenula activity was, the greater their selfreported social anhedonia also was during that same scanning visit.…”
Section: Discussionsupporting
confidence: 88%
“…The IC maps were then compared between groups on a voxelwise basis for statistical analysis using nonparametric permutation testing (5000 permutations), revealing group differences in network connectivity. To compare fMRI measures between two groups, a contrast matrix of network connectivity was constructed using general linear models (GLMs), with head motion parameters, age, sex, educational level, medication load, and the presence or absence of global signals as covariates ( p < 0.05, with false discovery rate [FDR] correction) [31] , [32] . We further analyzed functional connectivity in patients who took antidepressants and drug-naive patients separately ( Appendix Fig.…”
Section: Methodsmentioning
confidence: 99%
“…16 It consists of subcortical and fronto-cortical regions, 16 which are interconnected by white matter projections of the cingulum and medial forebrain bundle. Multiple neuroimaging studies have provided evidence for grey matter volume reductions in the reward system 20,21 and microstructural changes in the medial forebrain bundle 22,23 and the cingulum bundle 23,24 to be implicated in MDD.…”
Section: Psdmentioning
confidence: 99%